Festividad tradicional de la danza de los Negritos del centro poblado de Cochatama, Huácar – Huánuco - Serrano Escobal, Yoel (2025)
This research is based on an ethnographic and ethnomusicological study, with the main objective of comprehensively analyzing the current state, significance, organization, costume, choreography, and music of the “Negritos” dance from the rural community of Cochatama. The study is framed within a qualitative approach, adopting a descriptive level with an ethnographic design. Seven key informants participated in the research, including dancers, musicians, elderly individuals, and local residents. Observations revealed a growing distortion in various aspects of the dance, driven by efforts to make it more appealing to contemporary audiences, by arbitrary "innovations" introduced by certain musicians, and by the increasing popularity this cultural manifestation has gained. The results have allowed for a detailed description of the origins, current context, and significance of the dance, as well as of the key elements that shape this cultural expression: organization, costumes, and music. This study makes a significant contribution to addressing a gap in the field of ethnographic research.